2004
DOI: 10.1177/0898264303262650
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Communal Lifestyle on Depressive Symptoms in Late Life

Abstract: Both lifetime and current living conditions contribute to better mental health of women in the kibbutz at older ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
3
20
0
3
Order By: Relevance
“…The 20 items of this measure (Radloff, 1977) assess the extent to which participants have experienced depressive symptoms over the past 7 days: 1 ¼ rarely or none of the time (less than 1 day), 4 ¼ most or all of the time (5-7 days). The current study used a Hebrew translation (Blumstein et al, 2004), which has been used in previous research in Israel (e.g., Benyamini & Lomranz, 2004). In addition, to maintain measure consistency, the time frame was changed to ''how do you usually feel?''…”
Section: Methodsmentioning
confidence: 99%
“…The 20 items of this measure (Radloff, 1977) assess the extent to which participants have experienced depressive symptoms over the past 7 days: 1 ¼ rarely or none of the time (less than 1 day), 4 ¼ most or all of the time (5-7 days). The current study used a Hebrew translation (Blumstein et al, 2004), which has been used in previous research in Israel (e.g., Benyamini & Lomranz, 2004). In addition, to maintain measure consistency, the time frame was changed to ''how do you usually feel?''…”
Section: Methodsmentioning
confidence: 99%
“…The social or environmental resources are those on which individuals and social groups rely to cope with difficult situations. For example, several studies (Cornman et al 2003;Blumstein et al 2004) have shown that positive social interactions and involvement in social activities and community life not only protect against fear but are also associated with greater vitality, better perceived health, and a reduction in depressive symptoms and health problems.…”
Section: Discussionmentioning
confidence: 97%
“…Mortalidade -Do total, quinze estudos encontraram efeitos significativos da participação de idosos em atividades avançadas de vida diária e redução dos riscos de m orte 9,15,16,18,19,20,21,22,23,24,26,30 . No entanto, esses efeitos diminuíram ao longo do seguimento dos estudos, fato possivelmente relacionado ao avançar da idade 20 .…”
Section: Efeitos Da Participação Em Aavdsunclassified